Status dan Diskriminasi terhadap Anak di Luar Nikah Perspektif Ulama Fiqh - Samsul Arifin; Suaidi (Al-Adillah: Jurnal Hukum Islam, 2022)
The pros and cons of adultery are increasingly interesting to discuss. Especially the difference in views between the Constitutional Court and the MUI in deciding on the nasab relationship of the adulterous child. According to the Constitutional Court, children out of wedlock still have civil relations with men which can be proven based on science and technology and/or other evidence. Meanwhile, according to the MUI, to sue the biological father to support or receive inheritance, the lineage of the child does not need to be determined by the lineage with the biological father. This MUI decision refers to the opinions of scholars scattered in several tours. The method used in this study is a qualitative method, namely describing the views of fuqaha 'about adultery children. Data collection techniques used in this research are editing, coding, and tabulating. After the data has been collected, it is then analyzed using content analysis in the sense of capturing the implied message of one or several statements. To test the validity of the data in this study, the researcher took several steps, namely making careful observations, triangulating sources, and conducting discussions with colleagues. The finding of this study is that there are several opinions of fuqaha' who discriminate against adulterous children. From these findings, the researchers produced answers to the problem formulation. First, of the three issues related to adultery, the majority of jurists agree on the issue of lineage and inheritance. In terms of lineage, and inheritance, the child of adultery does not get the slightest rights from his biological father. Meanwhile, regarding the issue of adulterous children becoming prayer priests, the fuqaha' differed in opinion. Second, From some of the opinions of the scholars above, regarding the issue of an adulterous child becoming a prayer priest, it is Hanafiyah's opinion that discriminates more against an adulterous child. Likewise in the matter of lineage, although most scholars agree, including Imam Syafii, socially, the conclusion tends to discriminate against adulterous children, even though by argument their footing can be accounted for.